1981
DOI: 10.1212/wnl.31.3.243
|View full text |Cite
|
Sign up to set email alerts
|

Intensive monitoring in refractory epilepsy

Abstract: Forty patients with intractable seizures were studied in an epilepsy unit for an average of 8 weeks with video-electroencephalographic telemetry and continuous observation by trained personnel. Drugs were administered on the basis of antiepileptic drug measurements and seizure classification determined by clinical observation and telemetry. Seizure frequency was reduced in 24 patients (60%). Unrecognized seizure types were identified in 8 patients (20%), and diagnostic classification was changed in 19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

1982
1982
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 0 publications
1
36
1
Order By: Relevance
“…A small number of studies have also assessed the proportion of patients in whom VT resulted in a change in the preadmission diagnosis or management 1821. In the most recent and largest of these studies, Ghougassian et al reported that 58% of 131 patients admitted to a tertiary unit had a change from their provisional preadmission diagnosis due to VT 22.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have also assessed the proportion of patients in whom VT resulted in a change in the preadmission diagnosis or management 1821. In the most recent and largest of these studies, Ghougassian et al reported that 58% of 131 patients admitted to a tertiary unit had a change from their provisional preadmission diagnosis due to VT 22.…”
Section: Discussionmentioning
confidence: 99%
“…However, very few published studies specifically examined the proportion of patients in whom the inpatient VEM resulted in a change in the preadmission diagnosis or management (7). Sutula et al (7) reported 40 patients who were studied for an average of 8 weeks with video‐EEG monitoring. The diagnostic category was changed as a result of the monitoring in 19 (47.5%), and AEDs were changed in 25 (60%).…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of spikes and seizures was significantly greater in rat recordings (Hellier et al, 1998;Sutula et al, 1981;Wilson et al, 1996). Therefore, the need for extremely high sensitivity and specificity was not as critical in these rat models, and this was particularly true for the seizure detection algorithms that relied on spike frequency.…”
Section: Seizure Detectionmentioning
confidence: 99%